2016
DOI: 10.1002/hep.28835
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic stellate cells induce hepatocellular carcinoma cell resistance to sorafenib through the laminin‐332/α3 integrin axis recovery of focal adhesion kinase ubiquitination

Abstract: This study unveils a novel mechanism of sorafenib resistance depending on the α3β1/Ln-332 axis and requiring FAK ubiquitination, providing new insights into personalizing therapy for patients with HCC. (Hepatology 2016;64:2103-2117).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
78
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 27 publications
1
78
0
Order By: Relevance
“…In fact, the effects, resulting from FAK-dependent deregulation of EZH2 transcriptional repression of specific targets, may converge to reinforce HCC sensitivity to selective FAK inhibition possibly reducing both local tumor growth and distant metastasis. Furthermore, since Azzariti et al have recently reported 48 a novel mechanism by which Sorafenib may induce HCC cell resistance through Laminin-332/ α 3 integrin-dependent escape of FAK from ubiquitination and consequent degradation, it is plausible that pharmacological inhibition of FAK may also enhance Sorafenib therapeutic performance. This information provides a proof-of-concept that drugs acting against FAK and EZH2, either those already approved by Food and Drug Administration or new ones, could represent a therapeutic option for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the effects, resulting from FAK-dependent deregulation of EZH2 transcriptional repression of specific targets, may converge to reinforce HCC sensitivity to selective FAK inhibition possibly reducing both local tumor growth and distant metastasis. Furthermore, since Azzariti et al have recently reported 48 a novel mechanism by which Sorafenib may induce HCC cell resistance through Laminin-332/ α 3 integrin-dependent escape of FAK from ubiquitination and consequent degradation, it is plausible that pharmacological inhibition of FAK may also enhance Sorafenib therapeutic performance. This information provides a proof-of-concept that drugs acting against FAK and EZH2, either those already approved by Food and Drug Administration or new ones, could represent a therapeutic option for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…HCC cells secrete cytokines and chemokines to promote the activation of HSCs, while activated HSCs also produce chemokines to promote tumor cell proliferation and migration [21]. A recent study demonstrated that HSCs induce HCC resistance to sorafenib [22]. This indicates the potential involvement of tumor fibrosis in the development of resistance to sorafenib in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The mutual and symbiotic interconnections between anabolic CRC cells and highly abundant catabolic stromal fibroblasts or cancer- associated fibroblast (CAFs) favor the development of tumors and metastases [7]. Moreover, substantial studies recognize HSCs as the main matrix- producing cells in liver fibrosis [8]. …”
Section: Introductionmentioning
confidence: 99%